2021
DOI: 10.1021/acsaelm.1c00827
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Electrospun Polymer Composite Fibers for Microwave Absorption and Electromagnetic Interference Shielding

Abstract: Advancements in technology and widespread usage of electronic equipment have led to a vast hike in electromagnetic pollution such as electromagnetic interference (EMI). This has resulted in major concerns regarding human health and improper functioning of electronic devices. Therefore, high-performance EMI shielding materials are necessary to ensure human well-being and protect systems in domestic, civil, or military applications. Earlier, metals and alloys of metals served as EMI shielding materials. But due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 144 publications
0
28
0
Order By: Relevance
“…The diameter of these fibers ranges from nanometers to a few micrometers (μm). One of the primary advantages of electrospinning is its adaptability in processing, which allows it to create fibers with a variety of configurations and morphological structures [19,28]. Figure 1 represents the schematic diagram of the basic electrospinning set-up.…”
Section: Electrospinning Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of these fibers ranges from nanometers to a few micrometers (μm). One of the primary advantages of electrospinning is its adaptability in processing, which allows it to create fibers with a variety of configurations and morphological structures [19,28]. Figure 1 represents the schematic diagram of the basic electrospinning set-up.…”
Section: Electrospinning Setupmentioning
confidence: 99%
“…To understand the basic principle of the electrospinning process, consider a spherically charged droplet of a low-molecular-weight conducting liquid that is placed in a vacuum. The liquid droplet experiences two forces: (1) disintegrative repulsive Basic setup of electrospinning [28].…”
Section: Principlementioning
confidence: 99%
“…Due to their combined electrical conductivity, magnetic characteristics, and in particular, the nanofibrous structure, 1D electromagnetic nanofibrous composites can be used as effective electromagnetic shields. 22 However, only a few studies have reported the use of such materials as EMI shields. 27 Im et al 28 achieved maximum overall shielding effectiveness of 50 dB for fluorinated carbon black/CNF composites with 0.5 mm thick samples in the frequency range of 800 MHz−4 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective ways to incorporate metal oxide nanoparticles into 1D CNFs is electrospinning. Electrospinning is a fiber-spinning method that employs electrostatic forces to make long and continuous fibers of diameters in the nanometer to micrometer range. Nanofibers from polymer solutions or melts can be conveniently produced using this technique. Metal and metal oxide NPs can be incorporated into the nanofibers through electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…CMS effectually constrains the polysulfides using chemical interactions and enhances the reaction kinetics of polysulfide conversion. Additionally, the carbon nanotubes augment the electronic conductivity of the system, provide structural stability, and render physical entrapment of polysulfides. , Consequently, the cell demonstrated enhanced charge storage capability and electrochemical results with negligible self-discharge.…”
Section: Introductionmentioning
confidence: 99%